2022
DOI: 10.1002/ange.202205238
|View full text |Cite
|
Sign up to set email alerts
|

Directing the Morphology, Packing, and Properties of Chiral Metal–Organic Frameworks by Cation Exchange**

Abstract: We show that metal-organic frameworks, based on tetrahedral pyridyl ligands, can be used as a morphological and structural template to form a series of isostructural crystals having different metal ions and properties. An iterative crystal-to-crystal conversion has been demonstrated by consecutive cation exchanges. The primary manganese-based crystals are characterized by an uncommon space group (P622). The packing includes chiral channels that can mediate the cation exchange, as indicated by energy-dispersive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Recently morphology control through crystal-to-crystal conversion was demonstrated by postsynthetic cation exchange. 77 In this study, the hexagonal prism morphology crystals of Mn-AdDB MOF were obtained from the reaction tetrahedral pyridyl ligand, AdDB with MnCl 2 •4H 2 O. Under similar growth conditions, the reaction between AdDB and other transition metal salts: FeCl 2 , CoCl 2 , NiCl 2 , CuCl 2 , and ZnCl 2 , resulted in different morphologies with undefined structures (Figure 8).…”
Section: Postsynthetic Cation Exchangementioning
confidence: 91%
See 1 more Smart Citation
“…Recently morphology control through crystal-to-crystal conversion was demonstrated by postsynthetic cation exchange. 77 In this study, the hexagonal prism morphology crystals of Mn-AdDB MOF were obtained from the reaction tetrahedral pyridyl ligand, AdDB with MnCl 2 •4H 2 O. Under similar growth conditions, the reaction between AdDB and other transition metal salts: FeCl 2 , CoCl 2 , NiCl 2 , CuCl 2 , and ZnCl 2 , resulted in different morphologies with undefined structures (Figure 8).…”
Section: Postsynthetic Cation Exchangementioning
confidence: 91%
“…In addition to the above applications, the shape of the MOF crystals can also impact their optical properties, such as the absorption and emission spectra. 76,77 This can be useful in applications such as light harvesting or sensing.…”
Section: Controlled Morphologies Applicationsmentioning
confidence: 99%
“…The results also showed that ZIF-8 has a good protective effect against the enzymatic activity of HRP, (PQQ)GDH and urease [31]. An emerging MOF, chiral MOF [32][33][34], can also be used as a drug carrier, enabling better biocompatibility, bioavailability and biodegradability of chiral drugs [35]. A study focused on and highlighted the necessity for MOF-based nanoplatforms in tumor treatment, summarizing the effects of MOF-based radiotherapy, chemotherapy, chemo-dynamic therapy, photothermal therapy, photodynamic therapy, starvation therapy and immunotherapy, and combination therapy against tumors [36].…”
Section: Introductionmentioning
confidence: 87%
“…Recently, postsynthetic modification, as a complement to the traditional de novo synthesis protocol, has garnered a surge in interest due to its powerful ability to finely tune and modify the structures of prototype MOFs including pore size/shape/volume/surface. Thereinto, the cation-exchange approach has been acknowledged as a kind of convenient postsynthetic modification method for introducing new functions and/or tuning the pore nanospace of the prototype MOFs. For example, the replacement of Zn ions with Cu ions in the prototypical MFU-41 effectively enhances the adsorption capacity of small guests such as H 2 , O 2 , N 2 , and C 2 H 4 . By virtue of the cation-exchange strategy, , Thallapally group developed a Li + cation-functionalized MOF, [Li(H 3 O) 2 ]-[Zn 4 Li(L) 3 ]·6CH 3 OH (1-Li), by replacing the dimethylamine cations with Li + cations, which presents significantly improved CO 2 /CH 4 separation performance compared with the prototypical counterpart …”
Section: Introductionmentioning
confidence: 99%